Mobile Edge Service for Intersystem Handover - Pencheva, Evelina; Atanasov, Ivaylo; Kireva-Mihova, Denitsa; Trifonov, Ventsislav (International Journal of Engineering and Technology, 2018)
Multi-access Edge Computing (MEC) appears to be an integrating technology for radio access networks to enhance the access capacity, optimize network performance and improve quality of experience for end users. MEC distributes cloud capabilities for storage and computing in the radio access network, close to the end users. As far as the development of advanced Application Programming Interfaces is a key area, we propose a new mobile edge service that enables 3rd party control on intersystem handover. The proposed service enables authorized applications to initiate intersystem handover following specific policy. The service is described by information flows illustrating the basic functionality, data models that provide mediation functions, and handover state models considering some implementation issues.Â